Levels of Cadmium (Cd) and Copper (Cu) in the Blood of Rice Farmers in Pucung Kidul Village, Boyolangu District Tulungagung Regency - Qurrotu A’yunin Lathifah; Dora Dayu Rahma Turista; Lia Yosaneri Wina Nurtias; Widyanur Hafidhoh (Medical Laboratory Analysis and Sciences Journal, 2021)
Farmers in Pucung Kidul Village often use pesticides to eradicate pests, diseases, and weeds on plants. Pesticides contain several kinds of metals, including cadmium (Cd) and copper (Cu). High levels of cadmium in the blood can interfere with the process of erythropoiesis and heme synthesis caused by the accumulation of cadmium. While copper poisoning can cause degenerative processes in the brain and cirrhosis of the liver. This research is a descriptive study that aims to measure the levels of cadmium and copper in the blood of farmers in Pucung Kidul Village. Measurements were made using atomic absorption spectroscopy (AAS). The sample used in this study was 15 samples obtained by the purposive sampling technique. The results showed that all respondents did not use PPE and 2 respondents with a working period of > 5 years obtained cadmium levels from 15 samples, there was 1 sample with cadmium levels above the threshold, which was 0.047 mg/L. Meanwhile, the copper content of the 15 samples contained 1 sample with the copper content above the threshold, which was 1.27 mg/L. This shows that the proper use of PPE, also years of service, and age can affect blood levels of cadmium and copper. Where the longer the working period, the more exposure that occurs and causes high levels of cadmium and copper in the blood. With the results of this study, it is hoped that farmers will continue to use personal protective equipment (PPE) when using pesticides and wash their hands after using them.